Election, democratic legitimacy and regime stability in Bangladesh: A case study of the 10th general election - Quddus, S. M. Abdul (2014)
Bangladesh witnessed her 10th General Election held on 05 January 2014 with some remarkable incidents such as major political opposition parties did not take part in the polls hence more than 50% candidates of which mostly from the ruling party were elected MPs uncontested; voters turnout was very low - about 22-26% (www.amadershomoy.com); due to a lack of contesting candidates in some constituencies there was no vote at all!); election ends with chaos; local media, international communities and donor agencies expressed their dissatisfaction about the credibility of the election outcomes and the way election was conducted; and others. However, the ruling Awami League called the election a free and fair one and expressed its satisfaction about the election outcomes. This paper deals with the following research questions: (a) What is the political culture in Bangladesh and how does political culture influence election in the country? (b) Why Bangladeshi regimes feel encouraged to allow ‘electoral engineering’ or fail to meet international standards while conducting elections? (c) What are the consequences when elections fail to meet the necessary level of credibility and how to overcome these problems? The paper is based on empirical data collected mainly from personal observation of the 10th national election in Bangladesh as well as information from the Election Commission’s website and print and electronic media reports about the 10th General Election and democracy in Bangladesh. Data from published secondary sources have also been consulted. This paper argues that Bangladesh democracy is again at the crossroads as the provision of Non-party Caretaker Government (NCG) has been scrapped by the current regime from the Constitution despite resistance from the main opposition block. In fact, the 10th general parliamentary election under party government raised critical questions about the credibility of election, legitimacy of the regime, and stability of the government. The paper further argues that democracy has been provided with little room for expected development by uncouth party politics or political culture in Bangladesh. Although an interim arrangement, called the Caretaker Government system, was introduced for transition from dictatorship into democracy in 1991 and was relatively successful in holding three free and fair elections; it suffered setback in conducting the 4th General Election owing to composition imbroglio and was replaced by a military-backed Caretaker Government. Therefore, this paper draws the conclusion that though electoral system in Bangladesh has been changed from the Caretaker Government system to election under party government system, little qualitative change has taken place in the country’s political system and electoral arena and culture to have credible election, followed by democratic legitimacy and regime stability.